Demonstration and Characterization of Cyst-Like Structures in the Life Cycle of Trichomonas vaginalis - Beri, Divya; Yadav, Priya; Devi, H. R. Nandini; Narayana, Chinmaya; Gadara, Darshak; Tatu, Utpal (Frontiers in Cellular and Infection Microbiology, 2020)
Trichomonas vaginalis is the parasitic protozoan residing in the urogenital tract causing trichomoniasis, which is the leading non-viral sexually transmitted disease. Life cycle of the parasite has been traditionally described as consisting of motile and symptom-causing trophozoites which are sexually transmitted. Chemical and temperature perturbations in trophozoites have been shown to aid conversion to a form named pseudocysts, which is poorly studied and believed to be degenerative forms (Petrin et al., 1998). In the current study, we show the formation of viable cyst-like forms in stationary phase of T. vaginalis axenic culture. Like cysts from other protozoan parasites like Entamoeba histolytica and Giardia lamblia, T. vaginalis cyst-like structures (CLS) appear spherical, immotile, uniquely stains with calcofluor white, is resistant to osmotic lysis and detergent treatments. We used calcofluor white, a fluorescent stain which specifically binds to chitin, to score for the Cyst-like structures. We demonstrate and quantitate the processes of encystation as well as excystation in vitro by using flow cytometry; thus, completing the parasite’s lifecycle without any chemical/ temperature alterations. To probe the physiological role of CLS, we exposed parasites to vaginal pH and showed that trophozoites take this as a cue to convert to cysts. Interestingly, CLS could survive and stay viable in chlorinated swimming pool water as shown by an esterase activity-based FDA viability assay implicating the possibility of their role as environmentally-resistant structures with possible non-sexual mode of transmission of the parasite. Further, in presence of in vitro cervical cells, CLS rapidly excyst to trophozoites which completely abrogated the cervical cell monolayer in a dose-dependent manner. To further corroborate the presence of two distinct forms in T. vaginalis, we performed two-dimensional gel electrophoresis and global, untargeted mass spectrometry to highlight proteome differences. Finally, we show that symptomatic human patient vaginal swabs have presence of both T. vaginalis trophozoites and CLS; thus, highlighting the role of cyst-like forms in clinical infections. The study highlights the plasticity of the pathogen and its rapid adaption when subjected to stressful environmental cues. Together, these findings suggest an important role of cysts-like structures in the parasite’s life cycle, pathogenesis and transmission.